Guiding principles for writing good requirements / Zuriati Yusof - Yusof, Zuriati (2013)
In software development projects, stakeholders are usually not able to objectively describe their requirements for the proposed systems. They are not able to foresee the envisioned system when either a new system is developed or the existing system is enhanced. These inaccurate or poorly written requirements have resulted in exhaustive and time-consuming modifications, risks and cost increases, and disagreements among the stakeholders. Furthermore, it is essential that the requirements to be early constructed and clearly formulated in the software lifecycle. Nevertheless, a model for writing good requirements in natural language is not in place until to-date. Thus, this project is carried out to fill the gap by constructing a guiding principle for writing good requirements of software development projects in order to fulfill the needs of all stakeholders. The principle is based on good requirement characteristics identified and analyzed and the English syntax structures for writing requirements studied. The results of this project are vital to contribute as guidelines and references to facilitate practitioners such as analysts, engineers, architects, designers, developers, testers, including customers in constructing good requirements for any software development project implementations.